STRUKTUR KOMUNITAS IKAN KARANG PADA AREA TRANSPLANTASI TERUMBU KARANG DI KAWASAN TAMAN WISATA PERAIRAN KAPOPOSANG, KABUPATEN PANGKAJENE KEPULAUAN, SULAWESI SELATAN - Rahmat Maulana (JURNAL PERIKANAN TROPIS, 2022)
ABSTRACTThe reef fish community is a very important part of the coral reef ecosystem, both in terms of economy and ecology. The purpose of this study was to determine the structure of the reef fish community, including species composition, abundance and ecological index of reef fish based on their role (major, target and indicator) in the coral reef transplant area of Kapoposang Island. The research method used is the coral reef fish visual census method to determine the structure of the reef fish community. Observations were made only once with two transect withdrawals and two repetitions on each transect. The results of the observation of reef fish, overall found 48 species, 28 genera, and 15 families consisting of major, target and indicator fish categories. The highest species composition came from the major fish category, chromis viridis, 16.7% and 12.7%, while the lowest species composition came from fistularia commersonii, parepercis hexophtalma, cheilinus fasciatus, chaetodon kleinii, chaetodon collare with the same species composition value of 0.21% - 0.42% other species have a species composition ranging from 0.63% - 8.46 %. The largest abundance of fish came from the pomacentridae family with a value of 560 ind/400m² while the lowest fish abundance was 2 ind/400m² from the fistularidae and pingupidae families. The diversity index value is 3.2621 including the high diversity category, the uniformity index value is 0.8427 including the stable uniformity category, and the dominance index value is 0.0574 including the low dominance category.Keywords : Kapoposang Island, Community structure of reef fish, Transplantation of coral reef